Nations and Nationalism In History Textbooks of Indonesia For High School Students Grade XI - Ghuci, Ihsan; Kurnia Wahyu, Itama Citra Dewi (HISTORIKA, 2019)
This study aims to examine the narrative of nationalism in the textbook of the History of Indonesian High School Grade XI. The problems raised are (1) What is the understanding of nationalism in the Indonesian History textbook for high school students? (2) What is the understanding of nationalism, according to Ernest Gellner in Indonesian textbooks? (3) How teachers and students understand nationalism in the Indonesian History textbook? The research method used is that content analysis is a method for collecting and analyzing the text's content. The text referred to in this study is the Nation and Nationalism in the textbook of Indonesian history for grade XI. The approach used is nationalism. While the theory used is Ernest Gellner's theory, the will theory, mentioning that the soul, taste, and will are a subjective factor, cannot be measured by objective factors. The results showed that the textbook examines about as among them (1) politics for prosperity and glory. (2.) Political Youth (3.) Revolutionary nationalism.